An Orthodox Historicism? - Bonsor, Jack A. (Philosophy & theology, 1990)
This essay suggests the possible form of an orthodox historicism. The essay begins by examining the historicism of Heidegger and Gadamer. It then proposes how a theology might appear which places the faith in conversation with this historicism.